Harina de arroz (Oryza sativa), Garbanzo (Cicer arietinum), Sorgo (Sorghum vulgare) como sustitutos de trigo en la industria panificadora - Fernández Chávez, Jixon Estiven (2024)
The document was prepared based on the theme: rice flour (Oryza sativa), chickpea (Cicer arietinum), sorghum (Sorghum vulgare) as wheat substitutes in the baking industry. The objectives set were to describe the nutritional and sensory aspects of the different rice, chickpea and sorghum flours for the baking industry and to detail the cost-benefit feasibility. The determining conclusions that rice flour provides a significant amount of manganese, calcium and zinc, vitamin D, B complex vitamins and iron, which indicates that this flour is an excellent source of carbohydrates, particularly the whole grain variety. Chickpea flour offers the body complex carbohydrates, which are characterized by their gradual release, resulting in significant nutritional content. It includes minerals such as magnesium, potassium, vitamins (especially those of group B, with the exception of B12) and essential fatty acids such as omega 6 and sorghum flour, making it a powerful antioxidant due to its richness in B vitamins (such as thiamine, riboflavin and niacin) and vitamin E. In addition, it contains minerals such as calcium, phosphorus, zinc and iron. According to the sensory characteristics, the flours obtained a favorable response in terms of smell, flavor, and texture. Investment in the production and marketing of rice, chickpea and sorghum flours proves to be a viable option, requiring the implementation of an action plan with specified dates to proactively manage possible setbacks.